Maria Magdalene: between myth and reality - Calcín Figueroa, Eduardo (2013)
Much has been said about Mary Magdalene (or Mary Magdalene) over the centuries in the history of Christianity. Her name has been associated with various biblical images, identified as such with the repentant sinner, the prostitute turned, the penitent with long hair and abundant tears, the young woman “who chose the better part” at the feet of Jesus, the woman of alabaster jar which blessed Jesus at Bethany, which he forgave her sins because she showed a lot of love, which remained at the foot of the Cross when all left, the first to see the risen and ran to announce to everyone that Jesus was alive are all these women the same person? Who is Mary Magdalene? What are the most reliable sources to reconstruct the shape and life of Mary Magdalene? These are questions we try to answer in this essay